Serjania rzedowskiana (Sapindaceae-Paullinieae): a New Species from Michoacán, Mexico - Ferrucci, María Silvia (2016)
Serjania rzedowskiana (Sapindaceae-Paullinieae), a new species from the Zicuirán-Infiernillo Biosphere Reserve of Michoacán, Mexico, is described and illustrated. The novelty differs from its congeners by having fruits with 3 indehiscent, wingless cocci, and by its sub-transversely obovoid seeds that occupy less than half of the locule. In addition, micromorphological features of the leaves, flowers and pollen grains are investigated. The distinctive fruit morphology of this new species is discussed in relation to other species of Serjania. In addition, a key is provided to differentiate the new species from other Mexican Serjania with similar vegetative characters (i.e. trifoliolate leaves and flowering branchlets with three peripheral vascular cylinders).